The agreement between patient demands, surgeon recommendations, and the decision to perform blepharoplasty and rhinoplasty: A cross-sectional study in Ho Chi Minh City - Thanh Van, Nguyen; Dang Khoa, Tran; Anh Tuan, Ho Nguyen; Hoai Thuong, Cao Nguyen; Dang Dieu, Pham (Journal of Neonatal Surgery, 2025)
Background: The demand for cosmetic surgeries, particularly blepharoplasty and rhinoplasty, has risen significantly. However, the alignment between patient expectations, surgeon recommendations, and the final decision to undergo surgery remains underexplored. This study aimed to assess the agreement between patient demands, surgeon recommendations, and the decision to perform blepharoplasty and rhinoplasty. Methods: A cross-sectional study was conducted on 1676 patients admitted to KAT Cosmetic Surgery and Thanh Van Cosmetic Hospital from January 2018 to June 2019. Medical records were reviewed to evaluate patient demands, surgeon recommendations, and actual surgeries performed. Cohen’s Kappa coefficient was used to assess agreement among these factors. Results: Blepharoplasty demand was more prevalent (81.3%) compared to rhinoplasty (22.8%). Upper lid blepharoplasty (70.1%) and nasal bridge augmentation (17.4%) were the most requested procedures. There was substantial agreement between patient demands and surgeon recommendations for the single suture technique (kappa = 0.89) and dorsal hump reduction (kappa = 0.77). However, no statistically significant agreement was found between patient demands and the decision to undergo surgery. Conclusions: There was significant alignment between patient demands and surgeon recommendations but a weak agreement between patient demands and the actual decision to perform surgery. Thorough consultations are essential for ensuring patient satisfaction by aligning surgical outcomes with patient expectations.